Post-transcriptional regulation of the Pqs Quorum Sensing System in Pseudomonas aeruginosa - Panagiotopoulou, Dimitra (2024)
Pseudomonas aeruginosa is a leading cause of morbidity in patients with respiratory diseases and is a very frequent pathogen in medical device-associated infections. The adaptability and potent virulence of this pathogen are mainly attributed to virulence coordination at the population level by the three Quorum Sensing (QS) systems Las, Rhl, and Pqs, in conjunction with small, regulatory non-coding RNAs (sRNA). Regulation by sRNAs provides quick responses to environmental cues by altering gene expression at the post-transcriptional level, aiding to swift adaptation to new environments.